2003
DOI: 10.1080/0264041031000140383
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of shock attenuation during fatigued running

Abstract: The aim of this study was to examine shock attenuation before and after completing a maximal effort graded exercise test while running on a treadmill. Ten individuals ran before and after a maximal graded exercise test with running speed controlled between conditions. Transfer functions were calculated using surface-mounted accelerometers to represent shock attenuation. An accelerometer was mounted on the distal aspect of the tibia and another on the anterior aspect of the forehead. Ten strides were analysed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 1 publication
12
110
1
4
Order By: Relevance
“…For M2, tibial acceleration along the longitudinal axis of the tibia was also used to detect FS [14]. Thereby, minimum acceleration before the peak tibial acceleration defined FS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For M2, tibial acceleration along the longitudinal axis of the tibia was also used to detect FS [14]. Thereby, minimum acceleration before the peak tibial acceleration defined FS.…”
Section: Discussionmentioning
confidence: 99%
“…FS was identified when crossing a threshold of zero g, before peak tibial acceleration occurred (by a maximum 20 ms before peak tibial acceleration, to prevent false detection, Figure 1). Method 2 (M2) was conducted according to Mercer et al [14]. The tibial acceleration signal along the longitudinal axis of the tibia was also used to detect FS.…”
Section: Foot Strike Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercer et al 34 reported that when the subject was standing the axis of the accelerometer was aligned with the longitudinal axis of the tibia however with any manipulation of stride length, as can happen in fatiguing long distance running, the axis alignment became distorted. Although previous research has stated that this misalignment leads to minimal differences in acceleration Abt et al 1 Bergamini et al 17 Butler et al 24 Channells et al 12 Clansey et al 25 Clansey and Hanlon 26 Clark et al 27 Crowell et al 28 Derrick et al 29 Gullstrand et al 10 Laughton et al 30 Le Bris et al 31 Lee et al 32 Lee et al 5 McGregor et al 33 Mercer et al 34 Mercer et al 35 Mercer et al 36 Milner et al 37 Patterson et al 38 Stohrmann et al 22 Stohrmann et al 23 Tan et al 14 power spectral density (PSD) using a previously published method 44 . Using the aforementioned methods tibial acceleration has been successfully identified to be reduced in high arched runners when running in cushion trainers shoes compared to motion control shoes 24 and also decrease when provided as visual feedback to those running on treadmills 28 .…”
Section: Research Orientated Kinematic Output Parametersmentioning
confidence: 99%
“…It was identified in 6 of the 12 articles and is important considering the repetitive nature of running thus any alteration of the body's ability to absorb shock could lead to additional stresses being placed on joints and the onset of overuse injury 1 . Four of the six articles 1,29,34,35 calculated shock attenuation using the same transfer function utilising frequency domain analysis. All of these articles identified shock attenuation as the average transfer function across similar impact frequencies ranges (10-20 Hz for Abt et al 1 , Derrick et al 29 and…”
Section: Shock Attenuationmentioning
confidence: 99%